The change of lignin, neutral detergent fiber, and acid detergent fiber of palm frond with biodegumming process as fiber source feedstuff for ruminantia - Imsya, Afnur; Paluli, Rizki (Indonesian Animal Sciences Society, 2009)
This research was conducted to study the effect of substrat levels and incubation time on changes of mean of: lignin, neutral detergent fiber and acid detergent fiber content of palm frond. This research was done based on completely randomized design with 2 factors as treatments. The first factor was substrate levels ie: 5, 10 and 15 litters, the second factor was incubation times: 3, 5 and 7 days of incubation which resulted in reduction content of lignin. Result of this research showed that treatments gave significantly different influence (P<0.05) on lignin, neutral detergent fiber and acid detergent fiber of palm frond. The best treatment was 15 litter of substrate with 7 days incubation, resulted in: 9.22 % lignin, 38.56% neutral detergent fiber, and 32.19% acid detergent fiber of palm frond. It is concluded that substrate level and incubation time interaction in biodegumming process decreased the level of lignin, NDF and ADF in palm frond. Key words: Biodegumming, Lignin, Neutral Detergent Fiber, Acid Detergent Fiber